Skinfold thickness measurements and mortality in white males during 27.7 years of follow-up. Issue 11 (November 2018) - Loh, Wann; Johnston, Desmond; Oliver, Nick; Godsland, Ian
Abstract Introduction Obesity is a major risk factor for mortality from a range of causes. We investigated whether skinfold measurements were associated with mortality independently of variation in body mass index (BMI). Methods A prospective analysis of mortality in 870 apparently healthy adult Caucasian men participating in an occupational health cohort was undertaken. At baseline, skinfold measurements were taken at biceps, triceps, iliac and subscapular sites. Derived measurements included the sum of all four skinfolds and subscapular to triceps, subscapular to iliac and BMI to iliac ratios. All-cause mortality was analysed by Cox proportional hazards modelling and death in specific mortality subcategories by competing risks analysis. Results During a mean of 27.7 years follow up, there were 303 deaths (119 cancer, 101 arteriovascular, 40 infection, 43 other). In univariable analysis, BMI was associated with all-cause, cancer, arteriovascular and other mortality and subscapular skinfold with all-cause and arteriovascular mortality. On bivariable analysis, with inclusion of BMI, subscapular skinfold ceased to be a associated with mortality but iliac skinfold emerged as strongly, negatively associated with all-cause and arteriovascular mortality. In multivariable analysis, with inclusion of age, BMI, smoking, alcohol and exercise, iliac skinfold was negatively associated with all-cause (Hazard ratio HR 0.77, 95% confidence interval CI 0.66–0.90, p = 0.002), arteriovascular (HR 0.75, 95%CI 0.58, 0.97, p = 0.02) and infection (HR 0.63, 95%CI 0.42, 0.94, p = 0.02) death. Among obese participants (BMI ≥ 30 kg/m2 ), iliac skinfold of ≤9.7 mm was associated with a six-fold increase in all-cause mortality risk. Conclusion Low iliac skinfold thickness is an independent risk factor for all-cause mortality in adult white males with risk apparently concentrated among people who are obese.